Attitudes Regarding Pregnancy Among Vascular Surgery Trainees and Program Directors Based on a Survey of Vascular Residents, Vascular Fellows, and the Association of Program Directors in Vascular Surgery. (August 2022) - Maloni, Krystal; Calligaro, Keith; Reed, Amy; Vani, Kunal; Dougherty, Matthew; Troutman, Douglas
Introduction: We conducted a survey of vascular surgery (VS) trainees and program directors (PDs) to examine differing attitudes regarding pregnancy, starting a family, and work-life balance.Methods: A 20 question survey was e-mailed to VS residents (0+5), fellows (5+2) and PDs using Survey Monkey Inc. (San Mateo, California).Results: The survey was sent to 781 participants (608 VS trainees, 173 PDs) with a similar response rate among residents [39% (133/343)), fellows [37% (98/265)], and PDs [38% (65/173)]. Of the 296 total respondents, most were male [61% (181)] and ≤40 years old [81% (240)]. VS trainees and PDs believed their work load or scheduling-coverage issues significantly increased when a trainee or peer was pregnant [PDs = 73% (38/52); fellows = 66% (59/89); residents = 54% (38/71), 13 PDs, 7 fellows and 59 residents had never worked with a pregnant peer or trainee]. Male respondents overall were significantly more likely than females to opine that a pregnant vascular trainee or attending was less capable of performing her job while pregnant [28% (50/179) vs.16% (18/110); P = .024). Women overall reported each of the following factors more commonly than men as reasons for delaying childbearing: impairing professional advancement [42% (42/99) vs 14% (23/165); P < .001], limited time to devote to children [60% (59/99) vs 39% (64/165); P = .001], not wanting to burden peers or associates [36% (36/99) vs 13% (22/165); P < .001), extra stress [67% (66/99) vs 30% (50/165); P < .001], perceived negative view of peers and program directors towards pregnancy [29% (29/99) vs 1% (2/165); P < .001], and encouragement not to have children from peers or attending [15% (15/99) vs 2% (3/165); P < .001). More females than males overall regret their career choice in VS as it relates to starting a family [22% (24/107) vs. 12%; 21/170); P = .028]. When asked about the major barriers for female vascular surgeons who wanted to become pregnant, PDs cited an unsupportive home environment more than trainees [37% (24/65) vs 22% (51/231); P = .015], whereas trainees cited safety concerns affecting the pregnancy, such as radiation, more than PDs [71% (164/231) vs 43% (28/65); P < .001]Conclusions: There are significant differences in views toward pregnancy among males and females and among trainees and PDs overall. Contrasting gender-based perceptions of the impact of pregnancy on vascular training need to be addressed before adequate solutions to the challenge of work-life balance can be achieved. Significant opportunities exist for trainees and PDs to address these knowledge gaps.